Pengembangan Lembar Kerja Peserta Didik Fisika Berbasis Model Research Based Learning Untuk Meningkatkan Creative Thinking Skills di MAN Sebukar Kerinci - Anne Ryandhosi (Peneliti.net, 2023)
The lack of creative thinking skills of the learners in MAN Sebukar are caused by several factors, including the lack of teaching materials that support the formation of creative thinking skills of the learners, and the application of learning model which does not require students to be active in the learning process in accordance with the demands of 2013 curriculum. To solve these problems, it is necessary to develop a teaching material, in the form of worksheet based on research-based learning model to improve learners' creative thinking skills. The purpose of this study was to produce students worksheet -based on Research Based Learning to improve creative thinking skills which are valid, practical and effective to use in learning physics. The design of this study is research and development by using Plomp development model which consists of three phases. The first phase is the preliminary research, in which an front-end analysis, the analysis of learners, and materials analysis related to the problems in physics learning were conducted. The second phase is Prototyping phase, in which students worksheet based on research based learning model was designed on the material of gravity laws of Newton and work energy. The last phase is assessment phase, in which the practicalities and effectiveness of the product were tested. The results of prototyping phase showed that students worksheet based on research based learning model to improve the creative thinking skills of learners is valid by mean of 0.73. For the practicality, the mean of questionnaire responses learners towards the product was 80.26, categorized as very practical; the mean of questionnaire responses of teachers was 97.22, also categorized as very practical. The result of the assessment phase showed that the product met the criteria of effectiveness as the data obtained showed that there was improvement of learners competences: cognitive, affective, psychomotor, as well as creative thinking skills. The mean value of cognitive competence was 80.54; affective competence was 83.93; and psychomotor competence was 83.40. Meanwhile, the mean value of creative thinking skills improvement was average and low in every meeting.